Acid tolerance, proton permeabilities, and membrane ATPases of oral streptococci. - Bender, G R (1986)
Differences in acid tolerance among representative oral streptococci were found to be related more closely to the dynamic permeabilities of the bacteria to protons than to differences in the sensitivities of cell membranes to gross damage caused by environmental acidification. For Streptococcus mutans GS-5, Streptococcus sanguis NCTC 10904, and Streptococcus salivarius ATCC 13419, gross membrane damage, indicated by the release of magnesium from whole cells, occurred at pH values below about 4 and was rapid and extensive at pH values of about 3 or less. A more aciduric, lactic acid bacterium, Lactobacillus casei ATCC 4646, was more resistant to environmental acidification, and gross membrane damage was evident only at pH values below 3. Assessments of the movements of protons into S. mutans cells after an acid pulse at various pH values indicated that permeability to protons was minimal at a pH value of about 5, at which the average half time for pH equilibration across the cell membrane was about 12 min. The corresponding values for the less aciduric organism S. sanguis were pH 7 and 8.2 min, and the values for the intermediate organism S. salivarius were pH 6 and 6.6 min. The ATPase inhibitor dicyclohexylcarbodiimide acted to increase markedly the permeability of each organism to protons, and this action indicated that permeability involved not only the passive inflow of protons but also active outflow through the proton-translocating membrane ATPase. Membranes were isolated from each of the bacteria, and pH profiles for ATPase activities indicated pH optima of about 7.5, 7.0, 6.0, and 5.0 for S. sanguis, S. salivarius, S. mutans, and L. casei, respectively. Thus, the pH profiles for the enzymes reflected the acid tolerances of the bacteria and the permeabilities of whole cells to protons.